A new gastropod associated with a deep-sea whale carcass from São Paulo Ridge, Southwest Atlantic - Hasegawa, Kazunori; Fujiwara, Yoshihiro; Okutani, Takashi; Sumida, Paulo Yukio Gomes; Kawato, Masaru; Kitazato, Hiroshi (Zootaxa, 2019)
An unfamiliar gastropod was collected from a deep-sea whale carcass at the base of the São Paulo Ridge in the Southwest Atlantic by the manned research submersible Shinkai 6500, and is here described as a new species of the abyssochrysoidean genus Rubyspira, R. brasiliensis sp. nov., following morphological and molecular phylogenetic examinations. There are only two other known species in the genus, which occur together in the Monterey Submarine Canyon off California. The present new species was shown by the molecular analysis to be closer to one of the Californian species than the other. It was found aggregated on and around a whale carcass at a depth of 4204 m, which represents the deepest record of whale- fall ecosystems ever discovered.